2015 Annual IEEE India Conference (INDICON) 2015
DOI: 10.1109/indicon.2015.7443826
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble classifier approach for disease diagnosis using Random Forest

Abstract: Massive amount of diagnostic data is generated everyday as a part of daily diagnosis, related to various types of diseases and disorders. For knowledge discovery from this diagnostic data, efficient data mining techniques play a very important role. Ensemble classifier is one of the data classification techniques related to data mining, in which decision of multiple base classifiers is combined for accurate prediction of the presence or absence of abnormality. Here, we have considered retinal images of diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The result of crisp has also shown that we can diagnose the patient's low or high risk of disease [41]. Recently several neuro-fuzzy techniques have been reported in the literature [7], [9], [10] and [20] for classification of patterns.…”
Section: Currently Used Methods For Pulmonary Tuberculosis Diagnmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of crisp has also shown that we can diagnose the patient's low or high risk of disease [41]. Recently several neuro-fuzzy techniques have been reported in the literature [7], [9], [10] and [20] for classification of patterns.…”
Section: Currently Used Methods For Pulmonary Tuberculosis Diagnmentioning
confidence: 99%
“…Long -term lung damage is associated with delayed treatment of PTB, often clinically mistaken for nontuberculosis pneumonia due to symptom similarities and presentation of chest X -ray (CXR) [6]. They reported that a delay in treatment of more than twelve weeks would result in a greater extent of patients with serious TB, a higher mortality rate, and a more prominent disappointment in treatment [7] [8]. For some reasons [9] and [10], diagnosis of tuberculosis is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The RF (Pachange et al, 2015) is an assembly method, where multiple decision trees are combined to generate predictions. This method is based on building decision trees, where data are divided using the problem variables, applying some criterion that evaluates and maximizes the gain of information.…”
Section: Techniquesmentioning
confidence: 99%
“…Currently, data mining and machine learning techniques allow the exploration and analyzation of data patterns through statistical methods and artificial intelligence [ 1 , 2 , 3 ]. Researchers can obtain correlations and patterns from large data sets to create new knowledge with the help of machine learning and artificial intelligence [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%